Positive Selection Drove the Adaptation of Mitochondrial Genes to the Demands of Flight and High-Altitude Environments in Grasshoppers - Li, Xiao-Dong; Jiang, Guo-Fang; Yan, Li-Yun; Li, Ran; Mu, Yuan; Deng, Wei-An (Frontiers in Genetics, 2018)
Mitochondrial adaptions to flight and to high-altitudes remain largely unexplored in invertebrates. In grasshoppers, some related species fly and some do not; other related species are endemic to the Tibetan Plateau and some are not. These species are therefore ideal models in which to investigate whether positive selection on mitochondrial genes drives adaptation. Our molecular evolutionary analysis of the 13 mitochondrial protein-coding genes (PCGs) in 15 species of flying grasshoppers and 13 related flightless grasshoppers indicated that the mitochondrial genes of flying grasshoppers have been subject to strong evolutionary constraints and positive selection which is stronger than the flightless grasshoppers. we found evidence of significant positive selection in the genes ATP8, COX3, ND2, ND4, ND4L, ND5, ND6 in the flying lineages. Thus, our results suggested that continuous negative selection acting on grasshopper mitochondrial genes maintained important functions related to energy metabolism, while episodic positive selection allowed the mitochondrial genes to adapt to increased energy demands during the evolution of flight. Our analysis of 5 grasshoppers endemic to the Tibetan Plateau and 13 non-Tibetan grasshoppers indicated that more nonsynonymous nucleotide substitutions accumulated in Tibetan grasshoppers than in non-Tibetan grasshoppers. We also found evidence for significant positive selection in the genes ATP6, ND2, ND3, ND4, ND5 in the Tibetan lineages. Our result thus strongly suggested that, in grasshoppers, positive selection drives mitochondrial genes to better adapt both to the energy requirements of flight and to the high altitude of the Tibetan Plateau.